2001
DOI: 10.1542/peds.107.5.e79
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Spinal Bone Mineral Density in Adolescents of an Ultra-Orthodox Jewish Community in Brooklyn

Abstract: ABSTRACT. Objectives. Bone mass increases throughout childhood, with maximal bone mass accrual rate occurring in early to mid-puberty and slowing in late puberty. Prevention of osteoporosis and its morbidities depends primarily on the establishment of adequate peak bone mass. Physical activity, calcium intake, and vitamin D stores (from sunlight conversion of precursors of vitamin D and to a lesser degree from dietary intake) are vital determinants of bone mineral density (BMD). BMD is further controlled by ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 45 publications
(33 reference statements)
1
17
0
Order By: Relevance
“…Although weight bearing exercise is known to help avert osteoporosis in the general population, there seems to be a varying relationship in anorexia nervosa. Several studies have reported that physical activity [25][26][27] increases bone density, while in other studies of patients with anorexia nervosa, exercise showed no protective capacity regarding BMD. 28,29 Our inability to find a relationship does not necessarily exclude the importance of this variable in influencing BMD; it may reflect that weight-bearing exercise is only protective if menstruation and the endocrinologic milieu has also been preserved.…”
Section: Discussionmentioning
confidence: 93%
“…Although weight bearing exercise is known to help avert osteoporosis in the general population, there seems to be a varying relationship in anorexia nervosa. Several studies have reported that physical activity [25][26][27] increases bone density, while in other studies of patients with anorexia nervosa, exercise showed no protective capacity regarding BMD. 28,29 Our inability to find a relationship does not necessarily exclude the importance of this variable in influencing BMD; it may reflect that weight-bearing exercise is only protective if menstruation and the endocrinologic milieu has also been preserved.…”
Section: Discussionmentioning
confidence: 93%
“…In young and middle-aged men, 25OHD was weakly correlated positively with BMD at the lumbar spine and the hip (13). The relationship between the PTH level and the BMD in young and middle-aged adults was weak or non-significant (15,29,30). Thus, current PTH secretion does not seem to be a significant determinant of bone mass and microarchitecture in young adult men, although these men may be in the phase of slow bone loss (31).…”
Section: Discussionmentioning
confidence: 97%
“…Establishment of an adequate peak bone mass is important to avoid osteoporosis and its subsequent comorbidities in later life. 166 Landin and Nilsson found that children with fractures due to low energy trauma had a lower bone density in their cortical forearm bones than children without fractures. This difference was not evident in children with fractures due to high-energy trauma.…”
Section: Bone Mineral Density Bone Structure and Fracturementioning
confidence: 99%
“…193 A study of ultra-orthodox Jewish adolescents with very little physical activity, measured in walking hours, found that the lumbal BMD was significantly decreased, especially in boys. 166 The relationship between bone mineral density and child fractures have been analysed with different results 32,90 and is further discussed in the chapter on fracture.…”
Section: Activity Versus Inactivitymentioning
confidence: 99%